Paramount Gold and Silver Further Expands San Francisco Bulk Tonnage Potential at San Miguel: Shallow intercepts return over 3 times open pit cut-off grade; 49.3 m intercept grades 26 g/t Ag and 0.11 g/t Au (Marketwired, 2014)
This news release uses the terms "measured and indicated resources" and "inferred resources." We advise U.S. investors that while these terms are defined in, and permitted by, Canadian regulations, these terms are not defined terms under SEC Industry Guide 7 and not normally permitted to be used in reports and registration statements filed with the SEC. "Inferred resources" have a great amount of uncertainty as to their existence, and great uncertainty as to their economic and legal feasibility. It cannot be assumed that all or any part of an inferred mineral resource will ever be upgraded to a higher category. Under Canadian rules, estimates of inferred mineral resources may not form the basis of a feasibility study or prefeasibility studies, except in rare cases. The SEC normally only permits issuers to report mineralization that does not constitute SEC Industry Guide 7 compliant "reserves," as in-place tonnage and grade without reference to unit measures. U.S. investors are cautioned not to assume that any part or all of mineral deposits in this category will ever be converted into reserves. U.S. investors are cautioned not to assume that any part or all of an inferred resource exists or is economically or legally minable. This release and related documents may include "forward-looking statements" including, but not limited to, statements related to the interpretation of drilling results and potential mineralization, future exploration work at the San Miguel Project and the expected results of this work, estimates of resources including expected volumes and grades and the economic projections included in the project's PEA. Forward-looking statements are statements that are not historical fact and are subject to a variety of risks and uncertainties which could cause actual events to differ materially from those reflected in the forward-looking statements including fluctuations in the price of gold, inability to complete drill programs on time and on budget, and future financing ability. Paramount's future expectations, beliefs, goals, plans or prospects constitute forward-looking statements within the meaning of the United States Private Securities Litigation Reform Act of 1995 and other applicable securities laws. Words such as "believes," "plans," "anticipates," "expects," "estimates" and similar expressions should also be considered to be forward-looking statements. There are a number of important factors that could cause actual results or events to differ materially from those indicated by such forward-looking statements, including, but not limited to: uncertainties involving interpretation of drilling results, environmental matters, lack of ability to obtain required permitting, equipment breakdown or disruptions, and the other factors described in Paramount's Annual Report on Form 10-K for the year ended June 30, 2014 and its most recent quarterly reports filed with the SEC.